PENGARUH REVITALISASI PRODUK WISATA TERHADAP PREFERENSI MENGUNJUNGI LEMBAH BOUGENVILLE RESORT (Survei pada Pengunjung Lembah Bougenville Resort Kecamatan Lembang Kabupaten Bandung Barat) - Gantini, Kariza Devia; Setiyorini, Heri Puspito Diyah (THE Journal : Tourism and Hospitality Essentials Journal, 2012)
Bougenville Valley Resort is a tourist attraction in the Cibodas village, Lembang, West Bandung District. Bougenville Valley Resort has a tourist attraction in the form of a very beautiful valley. Despite this growth in the number of visits in the Valley Bougenville Resort has fluctuating percentage, due Bougenville Valley Resort experience landslide disasters in 2007 with a percentage decrease of -10.65% and decreased again in 2009. One of the efforts to improve and restore the number of visitors came to the Valley Bougenville Resort, is to do the revitalization of tourism products consisting of revitalization tourist attractions, revitalization amenitas and revitalization of accessibility that may affect the interest of tourists to visit a tourist destination (Nindyo Suwrano: 2008). The purpose of this study was 1) to obtain findings regarding the revitalization of the tourism product in Bougainville Valley Resort 2) To obtain findings regarding preferences visited Bougainville Valley Resort 3) In order to obtain a model of the revitalization of the tourism product of the preference visited Bougainville Valley Resort. This research is descriptive and verification, because the method used is explanatory survey method using ordinal. Teknik scale analysis used in this study is the analysis of the path (path analysis), the technique of using systematic random sampling through cross sectional method with samples taken as many as 100 visitors. The study of the hypothesis shows that the revitalization of the tourism product consists of tourist attractions, amenitas and accessibility has direct and indirect influence significantly to visit the Valley Bougenville Resort preference of 56.8%, while the remaining 43.2% is explained by other variables not examined in this study. Suggestions for tourist attraction Bougenville Valley Resort is a further enhance other programs like promotion to the level of preference visited Bougainville Valley Resort better and cooperate with government and private parties.